Analisis Dampak Perdagangan Bebas ASEAN Terhadap Pertumbuhan Ekonomi Regional Tahun 2017-2021 - Abyan Husain Saefurrahman; Zefanya Preticia (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
The country certainly cannot be separated from the name of international trade. ASEAN, which is an organization of countries in Southeast Asia, is interdependent with each other. Cooperation between ASEAN countries covers various fields such as economics, politics, socio-culture, security and education. However, the main motive for this interdependence is motivated by economic and political factors. This interaction can be created well because it is influenced by the national interests of each country. Economic growth is also one of the goals that every country always wants to achieve. There are several indicators of the theoretical framework in the economic growth of ASEAN countries, including Foreign Direct Investment, results of exports and imports or international trade, as well as the country's per capita income (GDP per capita). A single direct investment or capital investment from one country to another can also make a major contribution to a country's development, through the transfer of assets, technology and managerial skills to increase the country's economic growth. Meanwhile, imports and exports can increase state income and the state's financial circulation can circulate well. Gross Domestic Product (GDP) is also an important indicator as proof of whether a country is progressing or not. Therefore, this research functions to analyze the impact or influence of free or international trade and economic growth in the ASEAN region in 2017-2021. The data used in this research is secondary data, obtained from the results of literature studies, journals, books and official sites or websites. The method used in this research is the multiple regression analysis method (OLS). Based on the known methods used, supported by the data obtained, it can be seen that international trade factors have a major impact on regional economic growth in the ASEAN region.